Application Of Information Technology, Online Tracking System, And Timeliness to Customer Satisfaction in Freight Forwarding Companies - Olfebri Olfebri; Nasrullah Nasrullah; Okta Bagus Maulana; Ega Ananda Dwi Syahputra (Dinasti Review, 2025)
The purpose of this study was to determine the cost emphasis, the flow of distribution of goods, and the strategies used for customer satisfaction by meeting customer expectations. The population of this study was users of shipping services, with a sample size of 150 respondents. They are using quantitative methods with non-probability sampling techniques. Data collection was carried out through distributing questionnaires. The results of this study indicate that (1) Information Technology has a positive and insignificant effect on customer satisfaction. (2) The tracking system has a significant effect on customer satisfaction. (3) Timeliness has a significant and positive effect on customer satisfaction.